Serological detection of Toxoplasma gondii, Leishmania infantum and Neospora caninum in cats from an area endemic for leishmaniasis in Brazil - Marques de Sousa, Keyla Carstens [UNESP]; Herrera, Heitor Miraglia; Domingos, Iara Helena; Vilela Campos, Joao Bosco; Campanelli dos Santos, Isabela Maria [UNESP]; Neves, Haroldo Henrique [UNESP]; Machado, Rosangela Zacarias [UNESP]; Andre, Marcos Rogerio [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
An investigation was made into the occurrence of antibodies to Toxoplasma gondii, Leishmania infantum and Neospora caninum in 151 domestic cats, based on the indirect fluorescent antibody test (IFAT). Serum samples were collected from 151 domestic cats (65 free-roaming and 86 domiciled cats; 55 males and 96 females) in Campo Grande, Mato Grosso do Sul, Brazil between January and April 2013. IgG antibodies to T. gondii, L. infantum and N. caninum were found, respectively, in 49 (32.5%), 34 (22.5%) and 10 (6.6%) sampled cats. A positive correlation was found between T. gondii and N. caninum, T. gondii and L. infantum, and N. caninum and L. infantum (p < 0.05) infections. Also, a significant interaction was identified between gender and area of activity on the probability of T. gondii (p = 0.0324) infection. However, no significant interaction was observed between gender and area of activity on infections by either N. caninum or L. infantum. This study showed that cats from an area endemic for visceral leishmaniasis in Brazil are exposed to three different protozoans, two of which are causal agents of important zoonosis.

O presente estudo teve como objetivo investigar a ocorrência de anticorpos anti-Toxoplasma gondii, Leishmania infantum e Neospora caninum, em 151 gatos, por meio da Reação de Imunofluorescência Indireta (RIFI). Entre os meses de janeiro e abril de 2013, amostras de soro foram coletadas de 151 gatos domésticos (65 gatos errantes e 86 gatos domiciliados; 55 machos e 96 fêmeas), de Campo Grande, Mato Grosso do Sul, Brasil. Anticorpos IgG anti-T. gondii, anti-L. infantum e anti-N. caninum foram encontrados em 49 (32,5%), 34 (22,5%) e 10 (6,6%) gatos amostrados, respectivamente. Verificou-se uma associação estatisticamente significativa entre as infecções por T. gondii e N. caninum, T. gondii e L. infantum e N. caninum e Leishmania infantum (p <0,05). Além disso, foi observada uma interação significativa entre sexo, área de atividade na probabilidade de infecção por T. gondii (p = 0,0324). No entanto, não foi observada interação significativa entre sexo e área de atividade nas infecções por N. caninum e L. infantum. Este estudo mostrou que os gatos de uma área endêmica brasileira para leishmaniose visceral são expostos a três diferentes protozoários, sendo dois deles importantes agentes zoonóticos.
Keywords: Cats; Leishmania infantum; Neospora caninum; Toxoplasma gondii; serology; Brazil